Tetraspanin CD151 as a target for antibody-based cancer immunotherapy. (22nd March 2011) - Haeuw, Jean-François; Goetsch, Liliane; Bailly, Christian; Corvaia, Nathalie
Abstract : CD151 is a plasma membrane protein belonging to the tetraspanin superfamily which is expressed on normal cells such as endothelial cells and platelets and frequently overexpressed on cancer cells. It is known to be functionally linked to cancer metastasis. In humans, increased expression of CD151 is indicative of a poor prognosis in different cancer types. Whereas its mechanism of action remains obscure, CD151 was shown to regulate cell motility and adhesion through association with laminin-binding integrins such as α3β1 or α6β4. Several anti-CD151 mAbs (monoclonal antibodies) have been shown to display anti-metastatic activity in vivo . Inhibition of metastasis was not attributed to any effect of these mAbs on tumour cell growth, but was essentially attributed to inhibition of cell motility. We have generated anti-CD151 mAbs which can inhibit the tumoral growth in different xenograft cancer models. As expected, these mAbs were also able to inhibit metastasis in orthotopic cancer models. These data suggest that CD151 could function at multiple cancer stages, including not only metastasis cascade steps, but also earlier steps of primary tumour growth, thus reinforcing the interest of this innovative target in oncology. mAbs targeting CD151 may be of significant interest for cancer biotherapy.